Abstraction of Minahasan folklore in food tradition - Pamantung, Rina Palisuan; Mantau, Mercy; Sahetapy, Johan F.; Manangkot, Verra E. (Linguistics and Culture Review, 2021)
The main purpose of folklore is to convey present useful information and everyday life lessons in an easy way for the common people to understand. "The transmission process of folklore is still largely undocumented." Minahasan people still believe that Folklore become a philosophy in life. That philosophy never changes although time is changed until era 0.5. This research is entitled “Abstraction of Minahasan Folklore in Food”. The problems are the form and meaning of abstraction of Minahasan folklore in food. The method used is a qualitative method through an ethnography at the level of descriptive synchronic linguistics. An ethnographic approach was applied in data collection so that the form and meaning of Minahasan traditional food are in line with the concept of people’s of Minahasa. This research uses the Gastronomy linguistics approach and purposive sampling. The theory of Syntax by Givon (1994) and theory of meaning by Leech (1981) are used to analyze the data. The results showed that Minahasan Folklore consist of several titles are as follow: I royor si koki’ ,Toar Lumimuut, Si Naa en Jaa,Tumideng (Tumileng), Lingkambene (padi yang melambai), Wuwun Sewe, Tjarema, Sisil an dumoro’ in tjinamualian in tama i Maesa tanu in and Panagian.